Energy evaluation of R152a as drop in replacement for R134a in cascade refrigeration plants. (5th January 2017) - Cabello, R.; Sánchez, D.; Llopis, R.; Catalán, J.; Nebot-Andrés, L.; Torrella, E.
Highlights: R134a has been replaced with R152a in the high temperature cycle of a cascade refrigeration facility. The replacement performed was of the drop-in type. The refrigerant pair R152a/CO2 has been tested successfully in a wide range of operating conditions. No technical problems have arisen from using R152a. Energy results are similar for the cascade refrigeration plant working with R134a/R744 or R152a/R744. Abstract: An experimental comparison has been performed of a cascade refrigeration facility working with the refrigerant pairs R134a/R744 and R152a/R744. This kind of facility is suitable for industrial and commercial refrigeration applications. The high GWP refrigerant R134a has been substituted with the low GWP refrigerant R152a, in accordance with the new environmental regulations aimed at mitigating the Greenhouse effect. As both refrigerants belong to the family of HFC fluids, the replacement has been carried out as a drop-in. Apart from safety considerations, as R152a is included in the A2 group, the results of the wide range of tests conducted show that no special energy improvement or worsening is achieved, and that the replacement of R134a with R152a is technically and energetically feasible.